Kit Carson papers - Carson, Kit, 1809-1868.
Headquarters letterbook for the Navajo Expedition, commanded by Carson, begun at camp near Fort Wingate, N.M., (1863 July 11) and ended at Taos, N.M., (1864 May 17) . Includes photocopies of his baptismal, marriage, and burial certificates.
In part, positive photocopies.
Trapper, guide, Indian agent, and army officer.
Collection material in English, with Spanish.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Fortification -- New Mexico; Indians of North America -- New Mexico; Military bases -- New Mexico; Fort Wingate (N.M.); Taos (N.M.); Army officers; Guides; Indian agents; Trappers